ASSESSMENT OF ADHERENCE IN OUTPATIENTS WITH OPEN-ANGLE GLAUCOMA - Djordjević Jocić, Jasmina; Jocić, Hristina; Stoiljković, Milan (Acta medicae Medianae, 2025)
Glaucoma is chronic, progressive optic nerve neuropathy that leads to permanent defects of the visual field. Glaucoma still cannot be cured, however, with proper and correct use of prescribed therapy, it can be managed in a way to slow its progression and consequent loss of vision. Thus, having good adherence to recommended medications is of utmost importance for glaucoma patients. The study aimed to assess the degree of adherence to prescribed therapy for open-angle glaucoma in outpatients. In February 2019, one-month research was done at the Glaucoma Department of the Eye Clinic, Clinical Center Niši. It was performed on 77 outpatients using an anonymous, volunteer-based questionnaire consisting of 11 questions related to demographic and socioeconomic characteristics, disease duration, as well as adherence to recommended therapy and reasons for possible non-adherence. Out of the total outpatient number interviewed, 62.34% stated that they took their therapy as recommended, and 37.66% stated doing it not so regularly. Among those who were not taking therapy regularly, more were patients of older age (p = 0.00001; p < 0.05). No difference related to gender was found. Patients on multidrug glaucoma therapy were less adherent than those who used only one drug (p = 0.00034; p < 0.05). Better adherence was found in patients without comorbidities (87.5%) compared to those with some concomitant disease (35.14%), there was a statistically relevant correlation between these two parameters (p = 0.000002; p < 0.005). The most common reasons for non-adherence were adverse drug effects (100%), very long treatment period (89.66%) and patient’s forgetfulness. Relatively high, but not absolutely adequate degree of adherence is present among open-angle outpatients. Improvement of adherence can be achieved with optimal choice of therapeutic regimen, prescription of drugs with milder adverse effects, patient education about the course of disease and its possible consequences, i.e. blindness, as well as with emphasizing the importance of following recommended pharmacotherapeutic measures.